Influence of Organizational Innovation on Management Strategy: Strategic Change as a Mediator in the Education - Jemmy; Eryco Muhdaliha; Setyani Dwi Lestari; Selamet Riyadi; Agus Kusnawan (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
This study investigates the influence of organizational innovation on management strategy in the education sector, focusing on the mediating role of strategic change. Quantitative data were collected through a structured survey (Cronbach’s Alpha > 0.7) and analyzed using Structural Equation Modeling (SEM) with a sequential explanatory mixed-methods approach. Key relationships were identified: organizational innovation significantly impacts management strategy (β = 0.45, p < 0.01), while strategic change mediates this relationship (β = 0.30, p < 0.01). Qualitative data from semi-structured interviews with 20 educational leaders revealed three critical themes: strategic alignment with institutional goals, the importance of participative leadership, and barriers such as resource constraints and bureaucratic inertia. These findings highlight the necessity of integrating innovation with strategic change to optimize management practices. The study contributes to literature by validating the dynamic capabilities framework in the education sector and addressing gaps related to the operationalization of innovation. Practical implications include fostering participative leadership, aligning innovation with institutional objectives, and streamlining resources to support transformative strategies. Policymakers and educational leaders are advised to implement context-sensitive frameworks to sustain innovation and enhance institutional adaptability.